Parameter Estimation of Fractional Uncertain Differential Equations - Jing Ning; Zhi Li; Liping Xu (Fractal and Fractional)
In this paper, we focus on the parameter estimations and some related issues of a class of fractional uncertain differential equations. We obtain the parameter estimations of the considered equations by using rectangular and trapezoidal algorithms for numerical approximation of optimal problems. Subsequently, by taking the trapezoidal method as an example, the predicted variable–corrected variable method is used to solve fractional-order uncertain differential equations, and numerical solutions were demonstrated by using different <semantics data-eusoft-scrollable-element="1">α</semantics>-paths. Finally, by using the trapezoidal algorithm, we predicted the closing prices of Tencent Holdings for the entire year of 2023 and compared them with actual historical values, showcasing the applicability and effectiveness of this method in practical applications.